L- carnitine and trans-10, cis-12 conjugated linoleic acid on in vitro bovine embryo production and cryopreservation - Zolini, Adriana Moreira (2015)
High lipid content in embryo is associated with low freezing tolerance. This study assessed the effects of exogenous L-carnitine and trans-10, cis-12 (t10, c12) conjugated linoleic acid (CLA) on in-vitro development and cryotolerance of bovine embryos when added during different stages of in vitro production of embryos. For all experiments, embryos were produced in vitro using slaughterhouse cows oocytes. Cleavage rates on Day 3, blastocyst and advanced blastocyst (hatching/hatched blastocyst) formation rates on Day 7 were calculated from the total number of oocytes subjected to in vitro fertilization (IVF). Expanded blastocysts-stage embryos from each treatment were harvested on Day 7 and subjected to slow freezing. Embryo viability was assessed 24, 48 and 72 h after thawing. In experiment 1, fertilized oocytes were incubated with different L-carnitine concentrations (0.0, 0.75, 1.50 or 3.03 mM) in the presence or absence of fetal bovine serum (FBS). There was an improvement (P<0.05) on embryo development when 1.5 mM of L-carnitine was added to in vitro culture (IVC) medium. L-carnitine had also a positive effect (P<0.05) on post thaw embryo competence when supplemented at 0.75 and 3.03 mM during IVC. There was no interaction (P>0.05) between the effects of L-carnitine and FBS supplementation on IVC on embryo development and cryosurvival. Although FBS supplementation had increased blastocyst development (P<0.05), it reduced the reexpansion rates at 24, 48 and 72 h post thawing. In experiment 2, L-carnitine (0.75 mM) or CLA (100 mM) were supplemented during the first 96 h, last 72 h or throughout the entire IVC period. There was no effect of L-carnitine or CLA supplementation during different periods of IVC on embryo development and cryotolerance. In experiment 3, embryo development and cryosurvival were evaluated when oocytes were maturated in medium supplemented with L-carnitine (3.03 mM) or/and CLA (100 mM). No effect of L-carnitine and CLA supplementation during in vitro maturation (IVM) on IVP embryo development was detected. Although there was no effect (P>0.05) of L-carnitine supplementation on embryo cryotolerance, CLA showed a negative effect (P<0.05) on embryo cryosurvival when added during IVM. In conclusion, L-carnitine improved embryo cryosurvival viiiwhen added at 0.75 mM during IVC and CLA supplementation during IVM has a negative effect on post thaw embryo survival.